2010
DOI: 10.1038/npp.2009.226
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Stimulant and Antipsychotic Drugs on Striatal Fast-Spiking Interneurons

Abstract: Psychomotor stimulants and typical antipsychotic drugs have powerful but opposite effects on mood and behavior, largely through alterations in striatal dopamine signaling. Exactly how these drug actions lead to behavioral change is not well understood, as previous electrophysiological studies have found highly heterogeneous changes in striatal neuron firing. In this study, we examined whether part of this heterogeneity reflects the mixture of distinct cell types present in the striatum, by distinguishing betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 57 publications
7
53
1
Order By: Relevance
“…In primates, striatal interneurons have been reported to show spontaneous inhibitory responses in response to conditioned reinforcers (Joshua et al, 2008;Kimura et al, 1984), suggesting that spontaneous inhibition of NAc FSIs may be a functional correlate of behavioral reward processing. Interestingly, a study from Wiltschko et al (2010) reported that systemic administration of high doses of a D2 receptor antagonist, eticlopride, caused strong inhibition in the spontaneous activity rates of NAc FSI populations recorded in rats, consistent with the present results. Furthermore, we have reported previously that specific blockade of D2 receptors within the shell (but not core) division of the NAc is sufficient to switch nicotine aversion behaviors into rewarding effects (Laviolette et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In primates, striatal interneurons have been reported to show spontaneous inhibitory responses in response to conditioned reinforcers (Joshua et al, 2008;Kimura et al, 1984), suggesting that spontaneous inhibition of NAc FSIs may be a functional correlate of behavioral reward processing. Interestingly, a study from Wiltschko et al (2010) reported that systemic administration of high doses of a D2 receptor antagonist, eticlopride, caused strong inhibition in the spontaneous activity rates of NAc FSI populations recorded in rats, consistent with the present results. Furthermore, we have reported previously that specific blockade of D2 receptors within the shell (but not core) division of the NAc is sufficient to switch nicotine aversion behaviors into rewarding effects (Laviolette et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…To ensure only this cell type entered our data set, we recorded units with low baseline activity (Ͻ5 Hz), and the firing rates we observed (1.37 spikes/s Ϯ 1.25, means Ϯ SD) are consistent with previous studies (Barnes et al 2005;Berke et al 2004;Mowery et al 2011;Schmitzer-Torbert and Redish 2008;Sharott et al 2009). Furthermore, we noted that the spike waveforms of the recorded units showed peak to valley intervals (means Ϯ SE) of 735 Ϯ 57 s and peak widths of 372 Ϯ 15 s, which are in agreement with previously reported MSN extracellular waveform characteristics (Wiltschko et al 2010). We recorded from 35 neurons.…”
Section: Populations Of Msns Encode Vibrotactile Stimulus Frequency Dsupporting
confidence: 91%
“…Frontal and striatal abnormalities have been associated with ADHD. The underlying pathophysiology of ADHD may involve dysregulation of the noradrenergic frontocortical inhibition of dopaminergic striatal structures (Kelly et al, 2007;Wiltschko et al, 2010). 5-HT and melatonin perform a broad range of physiological functions.…”
Section: Introductionmentioning
confidence: 99%